Perceptions of students on the physical exams in clinical nursing practice - Maria de Fátima Lima de Oliveira; Waldemar Brandão Neto; Andrea Rosane Sousa Silva; Ana Virginia Rodrigues Veríssimo; Ana Márcia Tenório de Souza Cavalcanti; Estela Maria Leite Meirelles Monteiro (Universidade Federal do Ceará, 2016)
Objective: to understand the perceptions of students from an undergraduate course in nursing on the importance of physical exams in clinical nursing practice. Methods: a qualitative study with 12 students of a private institution. For data analysis, the method of interpretation of meanings was used, based on the hermeneutic-dialectic perspective. Results: directions have been identified which give the physical exam an objective dimension, in which the accuracy of propaedeutic techniques is essential, and a relational dimension in which to give meaning to human actions permeated by subjectivity, new forms of production clinical nursing care are used. Conclusion: the physical exam contributes to the development of critical thinking in nursing care for the safety of the patient and autonomy to act in the scope of the clinical practice.